Sprint profile of professional female soccer players during competitive matches: Female Athletes in Motion (FAiM) study - Vescovi, J. D. (Journal of Sports Sciences, 2012)
The aim of this study was to determine sprint profiles of professional female soccer players and evaluate how various speed thresholds impact those outcomes. Seventy-one professional players competing in full matches were assessed repeatedly during 12 regular season matches using a Global Positioning System (GPS). Locomotion =18 km/h was defined as sprinting and each event was classified into: Zone 1: 18.0-20.9 km/h; Zone 2: 21.0-22.9 km/h; Zone 3: 23.0-24.9 km/h and Zone 4: >25 km/h. Outcomes included: duration (s), distance (m), maximum speed (km/h), duration since previous sprint (min) and proportion of total sprint distance. In total 5,019 events were analysed from 139 player-matches. Mean sprint duration, distance, maximum speed and time between sprints were 2.3 ± 1.5 s, 15.1 ± 9.4 m, 21.8 ± 2.3 km/h, and 2.5 ± 2.5 min, respectively. Mean sprint distances were 657 ± 157, 447 ± 185, and 545 ± 217 m for forwards, midfielders and defenders, respectively (P = 0.046). Midfielders had shorter sprint duration (P = 0.023), distance (P = 0.003) and maximum speed (P < 0.001), whereas forwards performed more sprints per match (43 ± 10) than midfielders (31 ± 11) and defenders (36 ± 12) (P = 0.016). Forty-five percent, 29%, 15%, and 11% of sprints occurred in sprint Zones 1, 2, 3 and 4, respectively. This group of professional female soccer players covered 5.3 ± 2.0% of total distance =18 km/h with positional differences and percent decrements distinct from other previously identified elite players. These data should guide the development of high intensity and sprint thresholds for elite-standard female soccer players.